SALE OF SECOND-HAND AND REMANUFACTURED COMPONENTS OF CONSTRUCTION EQUIPMENT: AN EMPIRICAL STUDY OF USER PERCEPTION IN ANDHRA PRADESH - Sreedhar Polavarapu; Narasimha Rao Vemula (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
The construction industry plays a pivotal role in shaping infrastructure and development, contributing significantly to economic growth and urbanization. In recent times, the sector has been seeking innovative ways to maximize efficiency, reduce costs, and promote sustainability. One promising avenue is the exploration of second-hand and remanufactured components for construction equipment, which has the potential to bring about substantial benefits for both businesses and the environment. This study explores the utility, availability, and compatibility of second-hand and remanufactured components for construction equipment, aiming to determine their potential to enhance machine productivity and contribute to revenue growth. The research methodology employs quantitative analysis to collect data from second-hand dealers across Andhra Pradesh. Additionally, consumer behavior is observed during the purchase of second-hand components, with a focus on relevant focus groups in this region. The study reveals that customer awareness and understanding of the technical aspects, usability, price comparisons, and compatibility of second-hand construction equipment parts are limited. Due to the lack of accessible testing facilities for remanufactured parts, customers often rely on their instincts and past experiences. Despite this, customers generally hold a positive perception of purchasing second-hand or remanufactured components. Furthermore, the high costs and scarcity of original parts at authorized dealerships drive customers towards buying components from the second-hand market.